2016
DOI: 10.1080/1478601x.2015.1121875
|View full text |Cite
|
Sign up to set email alerts
|

Improving court-appearance rates through court-date reminder phone calls

Abstract: a lafayette Parish Criminal Justice Coordinating Committee, lafayette, usa; b department of sociology, university of louisiana, lafayette, usa; c university of louisiana, lafayette, usaCourt appearance of defendants is required for the criminal justice system to perform its necessary functions. Without a defendant's appearance in court, the adjudication of criminal charges cannot proceed. Research dating back to the 1960s indicates that the national average for court appearance of defendants is approximately 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…We grouped studies into those that qualified as an RCT or CCT per the QAT (Ben-Ami, 1978;Bornstein et al, 2013;Chivers & Barnes, 2018;Emanuel & Ho, 2021;Ferri, 2020;Fishbane et al, 2020;Lowenkamp et al, 2018) and those that were not RCT or CCT designs (Howat et al, 2016;Nice, 2006;O'Keefe, 2007;White, 2006;Williamson, 2017). Studies that were not RCT or CCT designs had effect sizes ranging from OR = 0.71 to OR = 0.39 (Cohen's d = -0.19 to Cohen's d = -0.51) and included the two largest effect sizes identified in our review (Howat et al, 2016;White, 2006). RCT and CCT study designs had effect sizes ranging from OR = 1.06 to OR = 0.55 (Cohen's d = 0.03 to -0.33) and included four studies with the smallest effect sizes (Ben-Ami, 1978;Bornstein et al, 2013;Chivers & Barnes, 2018;Lowenkamp et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We grouped studies into those that qualified as an RCT or CCT per the QAT (Ben-Ami, 1978;Bornstein et al, 2013;Chivers & Barnes, 2018;Emanuel & Ho, 2021;Ferri, 2020;Fishbane et al, 2020;Lowenkamp et al, 2018) and those that were not RCT or CCT designs (Howat et al, 2016;Nice, 2006;O'Keefe, 2007;White, 2006;Williamson, 2017). Studies that were not RCT or CCT designs had effect sizes ranging from OR = 0.71 to OR = 0.39 (Cohen's d = -0.19 to Cohen's d = -0.51) and included the two largest effect sizes identified in our review (Howat et al, 2016;White, 2006). RCT and CCT study designs had effect sizes ranging from OR = 1.06 to OR = 0.55 (Cohen's d = 0.03 to -0.33) and included four studies with the smallest effect sizes (Ben-Ami, 1978;Bornstein et al, 2013;Chivers & Barnes, 2018;Lowenkamp et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…All studies compared groups of people who received reminders to groups who did not on subsequent rates of failure to appear in court. Some studies found that reminders did reduce failures to appear (Bornstein et al, 2013;Fishbane et al, 2020;Howat et al, 2016) and other studies found that they did not (Chivers & Barnes, 2018;Lowenkamp et al, 2018). Despite the mixed findings of individual studies, two recent qualitative reviews-one of 13 court reminder programs (Thomas & Ahmed, 2021) and the other of pretrial support programs including but not limited to court reminders (Hatton & Smith, 2020)-generally conclude that reminders are effective.…”
Section: Court Date Remindersmentioning
confidence: 99%
“…Research on the effectiveness of pretrial supervision strategies has focused overwhelmingly on use of court notifications and electronic monitoring. Prior research suggests that court hearing notifications can reduce FTA rates, particularly when notifications occur via phone call or text message (Bechtel et al, 2017;Cooke et al, 2018;Elek et al, 2017;Ferri, 2019;Howat et al, 2016;Lowenkamp et al, 2018;Nice, 2006;Schnacke et al, 2012;White, 2006). Research on the impact of electronic monitoring on pretrial outcomes has produced less favorable results, with inconsistent effects on re-arrest and FTA outcomes, and higher rates of technical violations (Baumer et al, 1993;Cadigan, 1991;Sainju et al, 2018;Wolff et al, 2017).…”
Section: Research On Pretrial Supervisionmentioning
confidence: 99%
“…Yet, recent research demonstrates that releasing people without requiring them to pay bail does not result in increases in rates of failure to appear (FTA; Monaghan et al, 2020;Ouss & Stevenson, 2019). To be sure, FTAs are a problem for courts with some jurisdictions reporting rates ranging from 20% to 50% of cases (Davis, 2005;Cohen & Reaves, 2007;Cooke et al, 2018;Howat et al, 2016). Courts spend hundreds of hours and millions of dollars taking action against people who fail to appear (Bernal, 2017;Rosenbaum et al, 2012;Tomkins et al, 2012) including forfeiture of bond, extra fines, driver's license suspensions, and jail time (Bornstein et al, 2012;Crozier & Garrett, 2020).…”
Section: Addressing Failure To Appearmentioning
confidence: 99%
“…Some reminders simply include the time, date, and location for a person's upcoming hearing or trial while others also remind people of consequences for not appearing or encourage people to make a plan that will help them show up in court. Live phone calls also may afford the opportunity for people to ask questions and to provide extra information about logistical issues, such as parking or bus schedules (Cooke et al, 2018;Ferri, 2020;Howat et al, 2016;Lowenkamp et al, 2018;Rosenbaum et al, 2012;Schnacke et al, 2012;Tomkins et al, 2012). These programs generally show success, with some reducing FTA rates by as much as 30% or more (Bornstein et al, 2012;Rosenbaum et al, 2012;Schnacke et al, 2012).…”
Section: Addressing Failure To Appearmentioning
confidence: 99%